Penegakan Hukum Terhadap Tindak Pidana Narkotika di Kota Makassar: Efektivitas dan Faktor-Faktor yang Mempengaruhi - Rifaldi, Achmad; Pawennei, Mulyati; Husen, La Ode (Sovereign: International Journal of Law, 2024)
This research aims to identify and analyze the enforcement of laws against narcotics offenses in Makassar City, as well as the factors influencing such enforcement. The study employs empirical legal research methodology, primarily utilizing field research supported by collected data and interviews. The research was conducted in Makassar City. The findings indicate that law enforcement against narcotics and psychotropic offenses in Makassar City has not been fully effective. This is attributed to several influencing factors: the legal framework itself, law enforcement officials, facilities and infrastructure, the community, and cultural factors. Community awareness and support for law enforcement efforts in combating narcotics and psychotropic abuse are deemed necessary. Furthermore, improved alignment between prosecutorial demands and judicial verdicts is required, given that narcotics and psychotropic offenses pose a significant threat to society and jeopardize the future of the younger generation.